2010
DOI: 10.1523/jneurosci.5837-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fgfr2Is Required for the Development of the Medial Prefrontal Cortex and Its Connections with Limbic Circuits

Abstract: To understand the role of specific fibroblast growth factor receptors (FGFRs) in cortical development, we conditionally inactivated Fgfr2 or both Fgfr1 and Fgfr2 [Fgfr2 conditional knock-out (cKO) or double knock-out mice, respectively] in radial glial cells of the dorsal telencephalon. Fgfr1 and Fgfr2 are necessary for the attainment of a normal number of excitatory neurons in the cerebral cortex. The action of FGF receptors appears to be through increasing self-renewal of neuronal precursors within the ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 60 publications
3
66
0
Order By: Relevance
“…Western blot analysis showed that labels a band of 47-50 kD, and it was characterized by using immunohistochemistry in mouse (Stevens et al, 2010). Our staining with this antibody matched that from original descriptions of Pax6 immunostaining in the developing cortex (Gotz et al, 1998), our previous publications (Martinez-Cerdeno et al, 2012;Cunningham et al, 2013a), and more recent work from unrelated laboratories (Fukushima et al, 2014;Maury et al, 2015).…”
Section: Antibody Characterizationsupporting
confidence: 74%
“…Western blot analysis showed that labels a band of 47-50 kD, and it was characterized by using immunohistochemistry in mouse (Stevens et al, 2010). Our staining with this antibody matched that from original descriptions of Pax6 immunostaining in the developing cortex (Gotz et al, 1998), our previous publications (Martinez-Cerdeno et al, 2012;Cunningham et al, 2013a), and more recent work from unrelated laboratories (Fukushima et al, 2014;Maury et al, 2015).…”
Section: Antibody Characterizationsupporting
confidence: 74%
“…FGFRs are required during the postnatal stage of presynaptic differentiation in vivo FGFR2 and FGFR1 also regulate embryonic neuronal development, including neuronal precursor specification and proliferation (Paek et al, 2009;Gutin et al, 2006;Stevens et al, 2010b). To exclude the influence of embryonic events to presynaptic defects in Fgfr2b…”
Section: ) We Found That Fgfr2bmentioning
confidence: 99%
“…63). In addition, recent findings demonstrate that Tgfbr2 activity is required for axon formation and neuronal migration in the developing mammalian neocortex (64) and that expression of Fgfr1 and Fgfr2 determines brain size (65,66). Richtsmeier et al (67) have pointed out the analogy between human craniosynostosis and the simplification trend of cranial bone elements in synapsid evolution.…”
Section: Discussionmentioning
confidence: 99%